THE ROLE OF REGIONAL CLUSTERS IN THE SOLUTION OF TASKS OF IMPORT SUBSTITUTION - Aleksandr S. Voronov (Вестник Российского экономического университета имени Г. В. Плеханова)
The article considers standard legal features of shaping clusters in regional economy of the Russian Federation. The author puts forward principles of forming regional assigned cluster to tackle tasks of import substitution by using foresight technologies. The sequence of stages necessary to design the concept of regional assigned cluster was shown. The forms of providing information and consultative support to entities of innovation activity in the field of import substitution on the part of municipal, regional and federal authorities were identified. The proposed algorithm for building innovation-oriented regional cluster system on import substitution is an element of organizational mechanism aimed at shaping joint types of economic activity on the basis of regional organizational, managerial and marketing innovation. An example of a ‘nuclear’ map for potential clusters with description of lines and types of activity for all kinds of organizations was given in the article.